Teacher Management Implementation Using Simpatika in Creating Accuracy of Data Services - Muhammad Ali Usman; Saipul Annur; Mardeli Mardeli; Irsyad Irsyad; Devi Wulandari (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to analyze the implementation of the SIMPATIKA application in creating accuracy of data services at the Ministry of Religion, Banyuasin Regency. This research is descriptive research with a qualitative approach. The data were collected through interviews, observation, and documentation. At the same time, the data analysis used was the Male and Humberman data analysis model. The results of this study found that: (1) The application of the SIMPATIKA application to the madrasah in Banyuasin District under the auspices of the Ministry of Religion has been well implemented, which is directed/controlled directly by the head of the madrasah whose input is assisted by the madrasa operator. (2) The role of the SIMPATIKA application is essential for data processing, school administration management, e-rapport and so on for the accuracy of data services related to educators and madrasah education staff in Banyuasin District.